Female directors and risk-taking behavior of Indian firms. Issue 7 (24th February 2021) - Biswas, Shreya
Abstract : Purpose: This study examines whether female directorship on board is related to firm's risk-taking behavior in India. Design/methodology/approach: The study considers the top 500 listed companies in India during the period 2013 to 2018 for the analysis. The paper employs fixed effects as well as a dynamic panel data model to address the bias in the fixed effects model when the lagged risk outcome is included as an explanatory variable. Findings: The study finds that the presence of female directors on board is unrelated to the firm's risk-outcomes and the risk-adjusted return earned by the shareholders. The results are in line with the tokenism theory of board diversity. Having a higher share of female independent directors is also unrelated to the risk-taking behavior of firms. The findings are in contrast to the critical mass theory and the agency theory of gender diversity. The study does not rule out the possibility of female directors' risk-preferences being similar to those of male directors. Practical implications: The findings suggest that regulations related to having independent female directors may not add value for the shareholders in the short run. The business case for such stringent regulations in India on the gender diversity of boards remains unclear. Originality/value: This is the first study to analyze the relationship between gender diversity of boards and firm-level risk in India. Most of the studies have focused on gender diversity and firm performance in India. However, modern portfolio theory suggests that both risk and return are important as shareholders care about risk-adjusted returns.